Development of phenotype algorithms using electronic medical records and incorporating natural language processing - Liao, Katherine P; Cai, Tianxi; Savova, Guergana K; Murphy, Shawn N; Karlson, Elizabeth W; Ananthakrishnan, Ashwin N; Gainer, Vivian S; Shaw, Stanley Y; Xia, Zongqi; Szolovits, Peter; Churchill, Susanne; Kohane, Isaac (BMJ (Online), 2015)
Electronic medical records are emerging as a major source of data for clinical and translational research studies, although phenotypes of interest need to be accurately defined first. This article provides an overview of how to develop a phenotype algorithm from electronic medical records, incorporating modern informatics and biostatistics methods.